2012 IEEE 6th International Conference on Information and Automation for Sustainability 2012
DOI: 10.1109/iciafs.2012.6419908
|View full text |Cite
|
Sign up to set email alerts
|

Gait pattern analysis of an Asian elephant

Abstract: Elephants have to maintain stability of a body weighing 2700 kg - 4500 kg in a wide range of unstructured terrain conditions. To achieve this, the dynamic walking control strategies of an elephant should be able to manage the large inertial forces working on the leg muscles. Therefore, understanding the gait patterns of an elephant can indicate the possible robust control strategies that an elephant may be adopting by exploiting its body dynamics and kinematics. This paper presents a simple method to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The stance time percentage for each limb was about 75% (ranging from 72.64 to 76.09%). Temporal data from this study were consistent with those in the studies of Genin et al [5] and Wijasooriya et al [7] in that elephants may bear more weight on their forelimbs in order to support their massive body weight. This study also confirmed that Asian elephants spend a single limb swing phase of only approximately 25%, and distribute their body weight to the other three legs in order to maintain stability while accelerating the body forward.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The stance time percentage for each limb was about 75% (ranging from 72.64 to 76.09%). Temporal data from this study were consistent with those in the studies of Genin et al [5] and Wijasooriya et al [7] in that elephants may bear more weight on their forelimbs in order to support their massive body weight. This study also confirmed that Asian elephants spend a single limb swing phase of only approximately 25%, and distribute their body weight to the other three legs in order to maintain stability while accelerating the body forward.…”
Section: Discussionsupporting
confidence: 82%
“…The stride length of each limb was approximately 200 cm, ranging from 192.6 to 198.9 cm, with no significant difference between the fore and hindlimb on each side at a comfortable walking speed of average 1.1 ms -1 . This may confirm that elephants walk with a lateral sequence footfall pattern, and distribute their center of mass proportionally across all four limbs, as reported in previous studies [5][6][7]16] . It was somewhat surprising that in this study the average stride length on the right side was significantly longer than that on the left (P<0.05 for both fore limbs and hind limbs).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Kinematic gait measurements have been used widely by clinicians and researchers to qualitatively assess the degree of movement impairments resulting from musculoskeletal and neurological problems. Earlier kinematic studies of gaits in horses, dogs, and elephants [ 13 , 14 , 15 , 16 ] utilized two-dimensional motion analysis with video capture. Recently, a novel wireless inertial measurement unit (IMU) has been developed with a motion sensor that enables three-dimensional (3D) analyses of a body’s specific force, movement, and angular rate and is now widely used in studies of motion analysis [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%